(untitled) (Jurnal Natur Indonesia, 2026)
The genus (Sarcoscypha coccinea spp.), commonly known as Red Cup Fungi, is represented by ecologically significant saprotrophic species that contribute to wood decomposition and nutrient cycling in forest ecosystems. This study documents, for the first time, the presence of Sarcoscypha coccinea spp. in Goygol National Park, located in the Little Caucasus region of Azerbaijan, and provides a synthesis of its distribution, morphology, and ecological functions in a mountain forest environment. The primary objective of the research is to characterize the species occurrence within the park, evaluate its habitat preferences, and highlight its potential role as an indicator organism for forest ecosystem integrity. Field surveys were conducted in March 2024 within the humid montane forest belt between Aggol and Goygol. The specimens were found at 40.4051° N, 46.3315° E and 1,540–1,620 m above sea level on decaying hardwood substrates, particularly on fallen trunks and stumps of Fagus orientalis and Carpinus betulus. The study area is characterized by a cold, humid mountain climate with 600–900 mm of annual precipitation and brown forest soils rich in organic matter. The species occurred in mesic, shaded microhabitats with stable moisture levels, typically along streamside forest corridors. Morphological examination confirmed the species as S. coccinea spp., distinguished by its bright scarlet apothecia, cup-shaped hymenial surface, and ellipsoid ascospores with two Conspicuous guttules. Ecologically, it accelerates lignocellulosic degradation, enhances soil organic matter formation, and supports microhabitat diversity in montane forest ecosystems. Its occurrence in Goygol National Park reflects both the conservation value of the region and the relatively undisturbed saproxylic habitats that persist within it. This study underscores the need for future molecular phylogenetic analysis and systematic documentation of fungal diversity in Azerbaijan’s protected areas